As relações entre o autobiográfico e o ficcional e a incorporação de conceitos físico-cosmológicos na trama do romance Olho de Gato: duas propostas de análise e suas possibilidades de convergência - Oliveira, Gisele Silva (Universidade Federal de São Carlos, 2024)
This work aims to propose analyzes of Margaret Atwood's novel Cat's Eye, based on two main interpretative approaches. The first purpose is the reflections that the work raises around the relationships between the autobiographical and the fictional. It thus seeks to think about these relationships, based on the Bergsonian conception of memory, in order to examine the role of mnemonic activity as an element that mediates them. It also seeks to explore the notions of autobiographical novel, by Philippe Lejeune (2014), and autofiction by Serge Doubrovsky (1977), also using the critical perspective of Evando Nascimento (2010/2017) on these notions, with the aim of verifying the potential dialogue between them and the novel object of study. The second interpretative bias aims to investigate the incorporation of assumptions from physical-cosmological theories and their possible resignification in the service of the literariness of language. In the end, this work aims to verify and highlight possibilities of correlations and convergences between the two proposed analytical paths.
The relationships between the autobiographic and the fictional and the incorporation of physical-cosmological concepts in the plot of The Cat'S Eye romance: two analysis proposals and their possibilities of convergence
Keywords: Olho de gato; Autoficção; Romance autobiográfico; Discurso físico-cosmológico; Cat's eye; Autofiction; Autobiographical novel; Physical-cosmological discourse; LINGUISTICA, LETRAS E ARTES